Effect of Peanut (Arachis hypogaea L.) Anthocyanin Extract on Cell Surface Hydrophobicity and Hemagglutination of Escherichia coli in Acidified Buffer Solution - Barcelo, Jonathan Mazon (Silliman Journal, 2022)
The effects of peanut anthocyanin extract and commercial cranberry juice on the hydrophobicity and hemagglutination of Escherichia coli (ATCC 25922) in acidified buffer solution was investigated. Pure cranberry juice and peanut anthocyanin extracts containing >108.55 mg/mL cyanidin-3-glucoside (cyd-3- glu) equivalents significantly reduced the hydrophobicity of 2.78 x 109 CFU/mL E. coli after 8, 20 and 30 hours (ρ<0.01) compared to lower concentrations while a concentration of 144.73 mg/L cyd3-glu equivalents resulted in the best hemagglutination inhibition of the same bacterial density of E. coli in less than 8 hours. The results show that peanut anthocyanin extract reduces cell surface hydrophobicity and inhibits the hemagglutination of E. coli in a timedependent and dose-dependent mechanism through nonspecific interaction with the bacterial cell membrane.